2021
DOI: 10.3390/brainsci11070868
|View full text |Cite
|
Sign up to set email alerts
|

Structural Degradation in Midcingulate Cortex Is Associated with Pathological Aggression in Mice

Abstract: Pathological aggression is a debilitating feature of many neuropsychiatric disorders, and cingulate cortex is one of the brain areas centrally implicated in its control. Here we explore the specific role of midcingulate cortex (MCC) in the development of pathological aggression. To this end, we investigated the structural and functional degeneration of MCC in the BALB/cJ strain, a mouse model for pathological aggression. Compared to control animals from the BALB/cByJ strain, BALB/cJ mice expressed consistently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Two anti-c-fos antibodies were used to validate specificity of c-fos staining in the adult marmoset (see Table 1). These antibodies have previously been successfully used as a marker for neuronal activity in rodent, non-human primate, and human tissue (Sarkar et al 2021; Heukelum et al 2021; Lopez et al 2014). The polyclonal guinea pig anti-cFps antibody (1:250, Synaptic Systems, catalog #226004, RRID: AB_2619946) has a synthetic peptide corresponding to amino acids 2 to 17 of rat c-fos.…”
Section: Methodsmentioning
confidence: 99%
“…Two anti-c-fos antibodies were used to validate specificity of c-fos staining in the adult marmoset (see Table 1). These antibodies have previously been successfully used as a marker for neuronal activity in rodent, non-human primate, and human tissue (Sarkar et al 2021; Heukelum et al 2021; Lopez et al 2014). The polyclonal guinea pig anti-cFps antibody (1:250, Synaptic Systems, catalog #226004, RRID: AB_2619946) has a synthetic peptide corresponding to amino acids 2 to 17 of rat c-fos.…”
Section: Methodsmentioning
confidence: 99%
“…The final paper of this set of studies looked at a model for pathological aggression investigating the association of aggression with structural and functional degeneration in mice. Van Heukelum and colleagues showed that the midcingulate cortex was not activated during a resident-intruder test after massive structural degeneration [6]. Observing heightened levels of aggression in these mice, the authors highlighted the midcingulate cortex as a potential key area for pathological aggression.…”
Section: Introductionmentioning
confidence: 99%